Beyond Fat Mass: Exploring the Role of Adipokines in Rheumatic Diseases - Morena Scotece; Javier Conde; Rodolfo Gómez; Veronica López; Francisca Lago; Juan Jesus Gómez-Reino; Oreste Gualillo (The Scientific World Journal)
The cloning of leptin in 1994 by Zhang et al. introduced a novel concept about white adipose tissue (WAT) as a very dynamic organ that releases a plethora of immune and inflammatory mediators, such as adipokines and cytokines, which are involved in multiple diseases. Actually, adipokines exert potent modulatory actions on target tissues involved in rheumatic diseases including cartilage, synovial, bone and immune cells. The goal of this paper is to elucidate the recent findings concerning the involvement of adipokines in rheumatic diseases, such as rheumatoid arthritis (RA), osteoarthritis (OA), and systemic lupus erythematosus (SLE).